Criminal Liability of Perpetrators of Embezzlement in Position at PT. Tunas Baru Lampung (Study of Decision Number 96/Pid.B/2022/PN.Gns) - Zulfi Diane Zaini; Yulia Hesti; Bayu Chandra Wijaya (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Among several criminal acts related to property and goods, there is a crime known as embezzlement where abuse of trust dominates as the main element in the occurrence of this crime. The problem in this research is what factors cause the perpetrator to commit the crime of embezzlement in his position at PT. Tunas Baru Lampung based on Decision Number 96/Pid.B/2022/PN.Gns, What is the criminal responsibility for the perpetrators of embezzlement of office at PT. Tunas Baru Lampung based on Decree Number 96/Pid.B/2022/PN.Gns. The factor that caused the defendant to commit embezzlement was due to economic factors where the defendant wanted to control the goods and then sell them and the money from the sale would be divided into three and the money would be used by the defendant for their daily needs. The defendant is responsible for his actions pursuant to Article 374 of the Penal Code. Jo Article 55 paragraph (1) 1 of the Criminal Code, the defendant was sentenced to nine months in prison.